Neutrophil extracellular traps as innate immune reaction against the emerging apicomplexan parasite Besnoitia besnoiti - Muñoz Caro, Tamara; Hermosilla, Carlos; Silva, Liliana M. R.; Cortes, Helder; Taubert, Anja; Justus Liebig University Giessen (My University, 2014)
Besnoitia besnoiti infection in cattle is an important emerging protozoan disease in Europe causing economic losses and severe clinical signs, such as generalized dermatitis, orchitis, and vulvitis in affected animals. Neutrophil extracellular trap (NET) formation was recently demonstrated as an important effector mechanism of PMN acting against several invading pathogens. In the present study, interactions of bovine PMN with tachyzoites of B. besnoiti were investigated in this respect in vitro. For the demonstration and quantification of NETs, extracellular DNA was stained by Sytox Orange or Pico Green. Fluorescent illustrations as well as scanning electron microscopy analyses (SEM) showed PMN-promoted NET formation rapidly being induced upon contact with B. besnoiti tachyzoites. Co-localization of extracellular DNA with histones, neutrophil elastase (NE) and myeloperoxidase (MPO) in parasite entrapping structures confirmed the classical characteristics of NET. Exposure of PMN to viable, UV attenuated and dead tachyzoites showed a significant induction of NET formation, but even tachyzoite homogenates significantly promoted NETs when compared to negative controls. NETs were abolished by DNase treatment and were reduced after PMN preincubation with NADPH oxidase-, NE- and MPO-inhibitors. Tachyzoite-triggered NET formation led to parasite entrapment as quantitative assays indicated that about one third of tachyzoites were immobilized in NETs. In consequence, tachyzoites were hampered from active invasion of host cells. Thus, transfer of tachyzoites, previously being confronted with PMN, to adequate host cells resulted in significantly reduced infection rates when compared to PMN-free infection controls. To our knowledge, we here report for the first time B. besnoiti-induced NET formation. Our results indicate that PMN-triggered extracellular traps may represent an important effector mechanism of the host early innate immune response against B. besnoiti which may lead to diminishment of initial parasite infection rates during the acute infection phase.
Keywords: ddc:630